Video-assisted thoracic surgery for primary myelolipoma of the posterior mediastinum. Issue 1 (December 2016) - Himuro, Naoya; Minakata, Takao; Oshima, Yutaka; Tomita, Yuri; Kataoka, Daisuke; Yamamoto, Shigeru; Kadokura, Mitsutaka
Abstract Background Myelolipoma is an uncommon tumor comprising adipose tissue and normal hematopoietic cells and mainly occurs in the adrenal cortex. Mediastinal myelolipoma is very rare; we report a case of posterior mediastinal myelolipoma that required surgical resection. Case Presentation A 56-year-old male was diagnosed with a posterior mediastinal tumor by computed tomography. The tumor was originally noted in 2005, and during follow-up in March 2014, it was found to have increased in size. During consultation at our hospital, on magnetic resonance imaging (MRI), we considered the possibility that the tumor was malignant. Consequently, we resected the tumor by video-assisted thoracic surgery (VATS). The histopathological findings revealed that the tumor had undergone intrathoracic extramedullary hematopoiesis. However, after considering the patient's background and histopathological findings, we diagnosed the tumor as a thoracic extra-adrenal myelolipoma. Conclusions Pathological analysis was instrumental in clarifying the diagnosis. We recommend surgery as a treatment option for posterior mediastinal tumors.